Answer:
False
Step-by-step explanation:
Make me brainliest
Sent you a pic of the product of the expressions.
Answer:
sjshdsedhbehbeh i dont know
Step-by-step explanation:
The first one simplifies by collecting like terms to become:
7a²(4b²+9ab+10)
and the second one simplifies again by collecting like terms to become:
7u(16u²-49v²)
Got anymore questions, happy to help :)
Answer:
3
−
2
=
1
3v-2=1
3v−2=1
Solve
1
Add
2
2
2
to both sides of the equation
3
−
2
=
1
3v-2=1
3v−2=1
3
−
2
+
2
=
1
+
2
3v-2+{\color{#c92786}{2}}=1+{\color{#c92786}{2}}
3v−2+2=1+2
2
Simplify
Add the numbers
Add the numbers
3
=
3
3v=3
3v=3
3
Divide both sides of the equation by the same term
3
=
3
3v=3
3v=3
3
3
=
3
3
\frac{3v}{{\color{#c92786}{3}}}=\frac{3}{{\color{#c92786}{3}}}
33v=33
4
Simplify
Solution
=
1
Step-by-step explanation: